2013
DOI: 10.1111/exd.12157
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase is a novel target of delphinidin for the inhibition of UVB‐induced MMP‐1 expression in human dermal fibroblasts

Abstract: We investigated the reported antiphotoaging effects of the major anthocyanidin delphidin and sought to identify its specific molecular target during UVB‐induced MMP‐1 expression. Delphinidin treatment significantly inhibited UVB‐induced MMP‐1 expression in primary cultured human dermal fibroblasts (HDF), an effect associated with the suppression of MKK4‐JNK1/2, MKK3/6‐p38 and MEK‐ERK1/2 phosphorylation. Further investigation revealed that delphinidin significantly inhibited UVB‐induced ROS production and NOX a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…Accordingly, in this study, we investigated the ROS generation signalling pathway in replicative‐aged skin cells. Previous reports have demonstrated that increasing ROS levels in HDFs lead to the upregulation of MMP expression . Therefore, in this study, we confirmed that the expression of MMPs increased in replicative‐aged HDF cells (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Accordingly, in this study, we investigated the ROS generation signalling pathway in replicative‐aged skin cells. Previous reports have demonstrated that increasing ROS levels in HDFs lead to the upregulation of MMP expression . Therefore, in this study, we confirmed that the expression of MMPs increased in replicative‐aged HDF cells (Fig.…”
Section: Resultssupporting
confidence: 88%
“…The primary reason for the loss of skin barrier integrity and tissue erosion, associated with acute exposure to UV‐B irradiation, is the generation of ROS . Elevated ROS disturbs equilibrium between pro‐ and antioxidants in the cell and activates various intracellular signalling pathways, leading to photodamage . Therefore, new strategies to ameliorate UV‐B‐induced damage deserve examination.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dermal fibroblasts also produce ROS via NOXs in response to growth factors . Recently, NADPH oxidase was characterised as a novel target of delphinidin in the inhibition of UVB‐induced MMP‐1 expression in human dermal fibroblasts .…”
Section: Introductionmentioning
confidence: 99%